Analyzing extraneous problem solving performances of 6th grade primary students - GÜLBAĞCI DEDE, HANDE; ŞENGÜL, SARE (ELSEVIER SCIENCE BV, 2011)
The purpose of this study is to analyze the 6th Grade primary students' solving word problem skills that require extraneous knowledge. With this purpose in mind, 109 6th grade primary students from a primary school in Istanbul attended this research. Two types of test were used in this research. In the first test, the students were asked five word problems but in the second test an unnecessary data which was not necessary to solve these problems were added. The scores which were taken from tests which were carried out a week apart were compared by using paired-sampling t-test. The results of the research reveal the fact which is supported by the literature that students cannot distinguish that the extraneous information is not necessary for solving the problem and as a result they became less successful in solving extraneous problems than normal problems. (C) 2011 Published by Elsevier Ltd.
Keywords: Problem solving; Real-life problems; Extraneous problems; ARITHMETIC WORD-PROBLEMS